Study on the Material Properties of Inorganic Silicate Coating and Protective Effect on Ship Metal Structure. (November 2020) - Xia, Cheng; Dong, Kehai; Lai, Shuaiguang; Zhang, Tong; Yu, Hongbo
Abstract: In order to verify whether the coating can meet the stringent requirements of the ship's long sailing cycle, harsh environment, and various unfavorable factors such as fire conditions, physical and mechanical performance tests, endurance tests, and Micro and micro tests of the three coating samples were carried out. The hardness of the ZS2000, ZS hybrid and ZS1000 coatings measured by the experiment were ⩾8H, ⩾7H, ⩾3H, respectively; the thermal conductivity values of the three coatings are very low, respectively 0.074 W/(m·K), 0.034 W/(m·K) and 0.025 W/(m·K), which can meet the requirements of the engine in unexpected flame environment; the original adhesion of the coating is the best, but the adhesion of the coating is reduced after the damp heat cycle and the salt corrosion at room temperature, and the salt spray resistance, damp and heat resistance of the coating are good, and no obvious defect is observed; TG experiments have found that the remaining percentages of the three coatings ZS1000, ZS2000, and ZS hybrid are 85.29%, 80.72% and 77.90% respectively. The thermal stability of ZS1000 is the best, and the three coatings have the best remaining balance. The difference is not large, so they all have good thermal stability. Analyzing the results of a series of performance tests, it is found that the comprehensive performance of the ZS hybrid coating is better than that of the ZS2000 and ZS1000 coatings.